Experimentally Determined Effects of Technological and Service Factors on Stress-Induced Destruction OF Concrete Under Compression - Hoła, J. (Engineering Transactions, 2002)
In the paper, the effects of different technological and service factors on the levels of fracture-initiating stress σ_i and critical stress σ_cr in concrete under compression have been compiled. Experimentally determined ranges of the stresses are given. Technological and service factors contributing to a high or low level of the stresses have been grouped together. It is shown how some technological and service factors affect the fatigue strength of concrete. This is done for a few selected concretes on the basis of known levels of the fracture-initiating stress σ_i and critical stress σ_cr.